Immunotherapy with single agent nivolumab for advanced leiomyosarcoma of the uterus: Results of a phase 2 study. Issue 17 (25th April 2017) - Ben‐Ami, Eytan; Barysauskas, Constance M.; Solomon, Sarah; Tahlil, Kadija; Malley, Rita; Hohos, Melissa; Polson, Kathleen; Loucks, Margaret; Severgnini, Mariano; Patel, Tara; Cunningham, Amy; Rodig, Scott J.; et al.
Abstract : BACKGROUND: Immunotherapy has changed the therapeutic landscape in oncology. Advanced uterine leiomyosarcoma (ULMS) remains an incurable disease in most cases, and despite new drug approvals, improvements in overall survival have been modest at best. The goal of this study was to evaluate programmed‐death 1 (PD‐1) inhibition with nivolumab in this patient population. METHODS: This single‐center phase 2 trial completed enrollment between May and October 2015. Patients received 3 mg/kg of intravenous nivolumab on day 1 of each 2‐week cycle until disease progression or unacceptable toxicity. The primary endpoint was objective response rate. We assessed PD‐1, PD‐ligand 1 (PD‐L1), and PD‐L2 expression in archival tumor samples and variations in immune‐phenotyping of circulating immune cells during treatment. RESULTS: Twelve patients were enrolled in the first stage of the 2‐stage design. A median of 5 (range, 2‐6) 2‐week cycles of nivolumab were administered. Of the 12 patients, none responded to treatment. The overall median progression‐free survival was 1.8 months (95% confidence interval, 0.8‐unknown). The study did not open the second stage due to lack of benefit as defined by the statistical plan. Archival samples were available for 83% of patients. PD‐1 (>3% of cells), PD‐L1, and PD‐L2 (>5% and >10% of tumor cells, respectively) expression were observed in 20%, 20%, and 90% of samples, respectively. No significant differences were observed between pre‐ and posttreatment cell phenotypes. CONCLUSION: Single‐agent nivolumab did not demonstrate a benefit in this cohort of previously treated advanced ULMS patients. Further biomarker‐driven approaches and studies evaluating combined immune checkpoint‐modulators should be considered. Cancer 2017;123:3285‐90 . © 2017 American Cancer Society . Abstract : Although this study reveals a lack of benefit for single‐agent nivolumab in an unselected cohort of women, it has stimulated further investigations of novel combinations of immunotherapy in sarcoma patients. The results of this study will help guide patients and providers away from the use of nivolumab for off‐label use in this patient population in an era of significant health care costs.